HomeBase: Participation, Engagement, Alliance, and Social Validity of a Motivational Parenting Intervention. Issue 4 (2nd October 2019) - Frey, Andy; Small, Jason W; Lee, Jon; Crosby, Shantel D; Seeley, John R; Forness, Steve; Walker, Hill M
Abstract: This article examines the participation, engagement, alliance, and social validity of homeBase—a parent management intervention developed specifically to address parent engagement of elementary-level students. The intervention infuses motivational interviewing (MI) into its implementation procedures and trains behavioral coaches to use this approach as their primary interactive vehicle with parents. Process data from participants ( N = 120) assigned to one of the two homeBase intervention conditions were examined to better understand the following dimensions: parental participation and engagement, coach–parent alliance, and the satisfaction of the homeBase intervention. Results indicate that parental participation was challenging in that 21 percent of the parents seemed unable to engage at all in the intervention. However, those who did participate were highly engaged and developed effective relationships with their coach. Parents perceived the homeBase intervention to be socially valid. There were also several interesting correlations among these measures that might potentially guide further research and practice. The authors recommend that school social work preparation programs and school districts consider including MI in curriculum and professional development efforts as a strategy for parental engagement.